Perlindungan Hak Anak Pasca Perceraian: Perspektif Hukum Keluarga Islam dan Kompilasi Hukum Islam - Ahmad Ikhsan Ramadhan; Diana Ramadani; Rizky Hilmansyah; Muhamad Mustajib Ramdani; Muhamad Arifin Ilham (CV SCRIPTA INTELEKTUAL MANDIRI, 2026)
The protection of children’s rights after divorce constitutes a crucial issue within Islamic family law and the Compilation of Islamic Law in Indonesia. Divorce often places children in a vulnerable position, particularly regarding custody, financial support, education, and psychological well-being. This study examines the protection of children’s rights after divorce from the perspective of Islamic family law and the Compilation of Islamic Law, emphasizing normative frameworks and their practical implementation. Using a normative juridical approach, this research analyzes statutory regulations, judicial decisions, and relevant scholarly studies related to post-divorce child protection. The findings indicate that although Islamic family law and national regulations provide a solid legal foundation for safeguarding children’s rights, significant challenges remain in enforcement, judicial consistency, and parental legal awareness. Judges play a decisive role in ensuring that court decisions reflect the best interests of the child by integrating legal, social, and moral considerations. Strengthening the protection of children’s rights requires regulatory harmonization, effective enforcement mechanisms, and a value-based approach rooted in justice and child welfare. This study contributes to the development of Islamic family law discourse by highlighting the need for a more responsive and child-centered legal framework.